2021
DOI: 10.1183/23120541.00414-2020
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of right atrial dilation in patients with pulmonary embolism

Abstract: AimsRight atrial (RA) dilation and stretch provide prognostic information in patients with cardiovascular diseases. We investigated the prevalence, confounding factors and prognostic relevance of RA dilation in patients with pulmonary embolism (PE).MethodsOverall, 609 PE patients were consecutively included in a prospective single-centre registry between 09/2008 and 08/2017. Volumetric measurements of heart chambers were performed on routine non-electrocardiographic-gated computed tomography (CT) and plasma co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The differences in the temporal resolution may account for the inter-technique variability in the measurements. A recent prospective study of 609 patients with acute PE [ 2 ] demonstrated the feasibility of performing fully automated RA volumetric analysis on non-ECG-gated CTPA. Whilst RA dilation was a frequent finding in this population, its prognostic performance was inferior compared to other risk stratification markers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences in the temporal resolution may account for the inter-technique variability in the measurements. A recent prospective study of 609 patients with acute PE [ 2 ] demonstrated the feasibility of performing fully automated RA volumetric analysis on non-ECG-gated CTPA. Whilst RA dilation was a frequent finding in this population, its prognostic performance was inferior compared to other risk stratification markers.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst RA dilation was a frequent finding in this population, its prognostic performance was inferior compared to other risk stratification markers. Moreover, in the above study [ 2 ], there were patients with co-morbidities that affected the atrial volumes (elderly male patients with cardiovascular comorbidities had higher volumes whilst cancer patients had lower volumes) and only 25% of the cases had corresponding echocardiography which adds to the difficulty of comparing CT measurement accuracy to other techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional (2DE) and three-dimensional (3DE) echocardiography are the most commonly employed noninvasive imaging techniques to evaluate RA size [11] , [12] , [13] . Volumetric assessment of the RA size may be more accurate than linear measurement because RA enlargement is asymmetrical.…”
Section: Ra Sizementioning
confidence: 99%
“…Measurement of right and left ventricular volume ratio may be a superior approach (13). Right and left atrium measurements on computed tomography (CT) are also known to have diagnostic and prognostic value for pulmonary vascular disease (14)(15)(16)(17)(18). Manual cardiac and pulmonary measurements are limited by their time-consuming nature (14), human error, observer variability (19,20), and observer experience leading to potentially inaccurate predictions and less frequent use.…”
Section: Introductionmentioning
confidence: 99%